2020
DOI: 10.1016/j.landurbplan.2020.103955
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and rural landscape: The case of Italy

Abstract: Highlights Authorities have presented contagion administrative with no reference to the type of development. The study investigates the correlation between infections and landscpe types. The results shows that a higher number of COVID-19 infections occurred in intesive landscapes. The paper suggests planning for more rural territory with lower energy inputs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 39 publications
4
40
0
Order By: Relevance
“…The spread of the virus has also been analysed in differently populated areas in relation to the territorial economic models. According to Agnoletti et al ( 2020 ), the presence of industrial and agro-industrial activities in Italy is correlated with the infection rate even after controlling for the demographic, economic and environmental characteristics of the provinces.…”
Section: Territorial Differencesmentioning
confidence: 99%
“…The spread of the virus has also been analysed in differently populated areas in relation to the territorial economic models. According to Agnoletti et al ( 2020 ), the presence of industrial and agro-industrial activities in Italy is correlated with the infection rate even after controlling for the demographic, economic and environmental characteristics of the provinces.…”
Section: Territorial Differencesmentioning
confidence: 99%
“…The lowest energy-intensive landscapes have an average of 49 infected per square kilometre and 28 per 10 000 inhabitants, compared to 134 per square kilometre and 37 per 10 000 inhabitants in more energy-intensive zones. 15 Mortality data related to the first wave of Covid-19 infection (from 1 February to 12 May 2020) confirm excess mortality of 61% in the main cities of Northern Italy. Excess mortality was calculated as the difference between the observed mortality in the period and the 5-year mean.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge this is the first study to investigate relationships between farming-related atmospheric pollution and COVID-19-related mortality. However, a 2020 study conducted in Italy found that the number of SARS-CoV-2 infections per unit population depended on the type of rural landscape [43]. The study classified rural All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…The desire to consume meat encourages the use of intensive farming resulting in increase emission of farming-related pollutants. As urged by the Lancet Report [44] and by Agnoletti et al [43] we need to move towards more sustainable agriculture with reduced livestock raising. Finally we note that intensive agriculture is also a major cause of biodiversity loss worldwide, which has been implicated in the emergence of SARS-CoV-2 and other viruses [44;52].…”
Section: Discussionmentioning
confidence: 99%